Hereditary alpha-tryptasemia in 101 patients with mast cell activation–related symptomatology including anaphylaxis - Giannetti, Matthew P.; Weller, Emily; Bormans, Concetta; Novak, Peter; Hamilton, Matthew J.; Castells, Mariana (Annals of allergy, asthma, & immunology, 2021)
Hereditary alpha-tryptasemia (HαT) is an autosomal dominant genetic trait characterized by multiple copies of the alpha-tryptase gene at the TPSAB1 locus. Previously described symptomatology involves multiple organ systems and anaphylaxis. The spectrum of mast cell activation symptoms is unknown, as is its association with specific genotypes. To describe clinical, laboratory, and genetic characteristics of patients referred for the evaluation of mast cell activation–related symptoms and genotype-confirmed HαT. We retrospectively describe clinical characteristics, baseline tryptase, and tryptase genotype in 101 patients. Patients were referred for mast cell activation–related symptoms and underwent genotyping to confirm diagnosis of HαT. Of 101 patients, 80% were female with average tryptase of 17.2 ng/mL. Tryptase was less than 11.4 ng/mL in 8.9% and greater than 20 ng/mL in 22.3% (range 6.2-51.3 ng/mL). KIT D816V mutation was negative in all subjects tested. 2α:3β was the most common genotype but did not correlate with tryptase levels. Unprovoked anaphylaxis was noted in 57% of the subjects with heterogeneous genotypes. Most common symptoms include gastrointestinal, cutaneous, psychiatric, pulmonary, cardiovascular, and neurologic. A total of 85% of patients were taking H1- or H2-antihistamines with partial symptom relief. Omalizumab was effective at suppressing anaphylaxis or urticaria in 94% of the patients. HαT encompasses a broad range of baseline tryptase and should be considered in patients with symptoms of mast cell activation and tryptase levels greater than 6.2 ng/mL. Patients may present with complex symptomatology including cutaneous, gastrointestinal, neurologic, and psychiatric symptoms and anaphylaxis, some of which respond to omalizumab.